New York mark-ups on petroleum products - Szymon Wlaslowski; Jane Binner; Monica Guiletti; Nathan Joseph; Birger Nilsson (Lund University, School of Economics and Management, Department of Economics, 2007)
This paper analyzes rigidities in the behavior of mark-up on petroleum products in the New York area using a new set of high-frequency data. We use a methodology that accounts both for deterministic and stochastic nature of petrol prices. The results indicate that the adjustment to the long run equilibrium mark-up is non-linear with adjustment speeds that are equal across regimes for two out of the three series analyzed. For one of the series the adjustment is beneficial for end consumers as we find that prices fall faster than they rise.
Keywords: C52; D40; L11; Q40; 330; asymmetric price transmission; petroleum; SETAR model; regime switching model